2015
DOI: 10.1109/jphot.2015.2402129
|View full text |Cite
|
Sign up to set email alerts
|

On Laser Ranging Based on High-Speed/Energy Laser Diode Pulses and Single-Photon Detection Techniques

Abstract: This paper discusses the construction principles and performance of a pulsed time-of-flight (TOF) laser radar based on high-speed (FWHM $100 ps) and high-energy ($1 nJ) optical transmitter pulses produced with a specific laser diode working in an "enhanced gain-switching" regime and based on single-photon detection in the receiver. It is shown by analysis and experiments that single-shot precision at the level of 2W3 cm is achievable. The effective measurement rate can exceed 10 kHz to a noncooperative target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 37 publications
0
46
0
Order By: Relevance
“…Obviously, the accuracy of the depth measurement depends on the transmitted laser pulse width and distance measurement resolution of the detector. With a pulsed laser source that has high energy (Er > 1 nJ) and narrow full width at half maximum (FWHM ~ 100 ps), single-shot depth resolution of < 2 cm is achievable [8]. The detector time measurement precision depends on the SPAD timing jitter (50 -100 ps) and the time gating precision.…”
Section: D Imager Operating Principlementioning
confidence: 99%
See 1 more Smart Citation
“…Obviously, the accuracy of the depth measurement depends on the transmitted laser pulse width and distance measurement resolution of the detector. With a pulsed laser source that has high energy (Er > 1 nJ) and narrow full width at half maximum (FWHM ~ 100 ps), single-shot depth resolution of < 2 cm is achievable [8]. The detector time measurement precision depends on the SPAD timing jitter (50 -100 ps) and the time gating precision.…”
Section: D Imager Operating Principlementioning
confidence: 99%
“…One part of the solution is to use optical filtering, carefully selecting the field of view of the receiver and using either a mechanical or electrical shutter. Range gating with fast electric shutter has been used in recent high-performance SPAD sensors to suppress the pile-up effect of unwanted photons arriving at the detector [7,8]. A SPAD imager operating principle that has been used in this work develops this idea further and decreases this time gating to the minimum.…”
Section: Introductionmentioning
confidence: 99%
“…The PDP is typically 5-2 % in the wavelength range of 800-900 nm meaning that approximately 50 photons per pulse are needed for a valid detection. This is about an order of magnitude less than what is needed in a typical linear receiver [4]. In addition, no separate analogue amplifier channel is needed which simplifies the receiver considerably.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, it has been shown that the single photon detection (single photon avalanche detector, SPAD) mode presents a very interesting option for the receiver of a pulsed time-of-flight (TOF) laser radar [1][2][3][4]. The main advantages of the single photon detection compared to linear detection (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation